2011
DOI: 10.1128/aem.02509-10
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variability in Culturable Pathogenic Vibrio spp. in Lake Pontchartrain, Louisiana, following Hurricanes Katrina and Rita

Abstract: We investigated the abundance, distribution, and virulence gene content of Vibrio cholerae, V. parahaemolyticus, and V. vulnificus in the waters of southern Lake Pontchartrain in Louisiana on four occasions from October 2005 to September 2006, using selective cultivation and molecular assays. The three targeted pathogenic vibrios were generally below the detection level in January 2006, when the water was cold (13°C), and most abundant in September 2006, when the lake water was warmest (30°C). The maximum valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 76 publications
4
34
0
1
Order By: Relevance
“…This is consistent with the significant relationships previously identified between turbidity and V. parahaemolyticus abundance (30,31,33,47,54). A positive association with turbidity is consistent with expectations because vibrios, like many other bacteria, are frequently attached when in the aquatic environment (16).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with the significant relationships previously identified between turbidity and V. parahaemolyticus abundance (30,31,33,47,54). A positive association with turbidity is consistent with expectations because vibrios, like many other bacteria, are frequently attached when in the aquatic environment (16).…”
Section: Discussionsupporting
confidence: 80%
“…Regression models incorporating an interaction between temperature and salinity were explored but did not significantly improve overall goodness-of-fit or otherwise provide an interpretation for the unexpected findings. Some studies have identified a significant relationship between vibrios and salinity (6,12,30,31,60,69,79), while others did not (47,60,66,68), so the relationship with salinity may be variable and complex. For example, Griffitt and Grimes (unpublished data) found that large salinity shifts, as seen during the opening of the Louisiana Bonnet Carré Spillway following the Mississippi River floods of 2011, can cause detectable and significant change in the relative numbers of pathogenic vibrios.…”
Section: Discussionmentioning
confidence: 99%
“…Positive relationships have been described between temperature and total vibrios in the waters of Germany (58,59), North Carolina (31,55,60,61), the country of Georgia (62), the state of Georgia (63), Italy (64,65), South Africa (66), and Germany (47). Interestingly, negative correlations have also been described between temperature and total vibrios in the waters of India (46,67) and Louisiana (68). Temperature has also been positively correlated to total vibrios in mussels (59) and sediment (47,64,69).…”
Section: Other Vibriosmentioning
confidence: 80%
“…Strong correlations between the occurrence of Vibrio spp. and temperature, salinity, chlorophyll a, rainfall, and dissolved oxygen have been reported repeatedly (51,52,53,54,55,56,57), and such measures, therefore, have significant potential for the use as early warning and monitoring systems to predict outbreaks of cholera.…”
Section: Zooplankton Taxamentioning
confidence: 99%